Both electric field and temperature independent behavior of piezoelectric property of Pb(Ni1/3Nb2/3)O3–PbTiO3. (January 2015) - Pan, Zhao; Chen, Jun; Fan, Longlong; Wang, Qi; Liu, Laijun; Fang, Liang; Xing, Xianran
Graphical abstract: Highlights: Temperature dependence of strain under unipolar cycling have been investigated in the (1 − x ) Pb(Ni1/3 Nb2/3 )O3 – x PbTiO3 solid solutions. The value of large-sigonal d 33 is of nearly a constant (∼520 pm/V) and keeps in approximately a plane in the ranges of both temperatures from RT to 100 °C and electric field from 0.0 to 2.0 kV/mm. Abstract: The temperature stability of electromechanical properties is an important issue of major concern for the design of actuators. In this paper, temperature dependence of ferroelectric properties have been investigated in the (1 − x )Pb(Ni1/3 Nb2/3 )O3 –x PbTiO3 ( x = 0.30–0.38) solid solutions. Interestingly, the unipolar strain in the composition of x = 0.38 shows a good linear relationship with increasing electric field, and the large-signal d 33 is independent with increasing temperature from room temperature to 100 °C. Furthermore, it also exhibits a very high piezoelectric coefficient d 33 = 450 pC/N near the morphotropic phase boundary. All above indicates the present system of (1 − x )Pb(Ni1/3 Nb2/3 )O3 –x PbTiO3 may be a kind of potential application for precisely controlling actuators.